101k views
0 votes
4. Simplify the expression: (2x)º

A.) 2

B.) 2x

C.) 1

D.) x

E.) 1
___
X

User Deepesh
by
5.6k points

1 Answer

1 vote

Answer:

The Answer is option C.) 1


(2x)^(0) = 1

Explanation:

Given:


(2x)^(0)\\

Solution:

Law of Indices:


(x* y)^(a) = x^(a)* y^(a)

Also,


a^(0) =1\\or\\(anything)^(0) = 1.......Always

Now we have,


(2x)^(0)=(2^(0)* x^(0))\\\\(2x)^(0)=(1* 1)\\\\(2x)^(0)=1\\\\\therefore (2x)^(0)=1

The Answer is option C.) 1


(2x)^(0) = 1

User Paulin Trognon
by
5.8k points